Percieved Challenges Associated with Elearning Platforms and Coping Mechanisms among Students at the University of Ibadan, Nigeria - Esther JP , Ayomo Folakemi; Adewale, Agbonjinmi Lawrence; Babafemi , Macaulay Oluropo; Adejoke, Oyekan Mojisola; Oluwaseyi, Aibinuomo Ayomide; Samson, Olafusi Oluwatosin (American Journal of Biomedicine and Pharmacy, 2024)
Introduction: The outbreak of the COVID-19 pandemic in early 2020 disrupted educational systems worldwide, forcing institutions to transition rapidly from traditional in-person learning to online eLearning platforms. In Nigeria, the University of Ibadan, like many other institutions, adopted this approach to ensure continuity in education despite the pandemic-related restrictions. However, this sudden shift posed significant challenges for students, particularly in a developing country context where issues such as inadequate internet infrastructure, limited access to digital devices, and financial constraints are prevalent. This study aims to explore the perceived challenges associated with the use of eLearning platforms and the coping mechanisms employed by students at the University of Ibadan during this period. Understanding these challenges and coping strategies is crucial for informing future policies and interventions that can enhance the effectiveness of eLearning in higher education, especially in resource-constrained settings. Objective: The study aims to investigate the perceived challenges associated with eLearning platforms and the coping mechanisms among students at the University of Ibadan, Nigeria. Method of Data Analysis: A cross-sectional survey was conducted among consenting undergraduate and postgraduate students at the University of Ibadan. Descriptive statistical analysis was used to assess knowledge, attitude, and perception scores among 420 respondents. Associations between demographic characteristics and perceived challenges, as well as coping strategies, were analyzed. Result: The study revealed that the majority of respondents were female (61.2%), with a mean age of 22.3 ± 3.4 years. The majority (66.7%) earned N25,000 or below monthly, and mobile phones were the most commonly used devices for eLearning (98.3%). Zoom was the most frequently used platform (87.1%), followed by WhatsApp (73.3%) and Google Meet (70.7%). Significant associations were found between sex (p-value = 0.023), monthly income (p-value = 0.033), and age (p-value = 0.047) with the perceived challenges. However, no significant associations were observed between demographic characteristics and coping strategies. Conclusion: The study highlights the challenges faced by students at the University of Ibadan in using eLearning platforms, particularly in relation to internet connectivity and financial constraints. Addressing these issues is essential to improving the effectiveness and user experience of eLearning platforms in higher education.